Variance in Approach Toward a 'Sustainable' Coffee Industry in Costa Rica. - Vogt, Melissa (Ubiquity Press, 2019)
"The monograph considers influence over time of Fairtrade and Rainforest Alliance in 10 Costa Rican coffee farming communities. In-country perspectives and relevant historic and contemporary literature inform findings. Misaligned intentions to outcomes; different sustainability approaches; and variable influence is observed. There is opportunity to: consider when certifications are most useful; develop locally relevant standards; vertically integrate sourcing chains; consider how complementary mechanisms can be used alongside, or to improve certification approach. Sustainability of coffee as a cash crop, considering influence on biodiversity, and the possible implication of reduced coffee crop density for consumers, the market and farming landscapes, is considered."